Comparing subject-specific mastery motivation in Hungary and the Republic of Moldova - Calchei, Marcela; Amukune, Stephen; Józsa, Krisztián (Frontiers in Education, 2024)
Research on mastery motivation has documented its importance in personality development, school achievement, yethowever, there is little research that examines school subject-specific specifically in cross-cultural research. The objective of this study was to investigate the school subject-specific nature of mastery motivation in the context of middle and secondary school, grades 5, 7 and 9 from Hungary (N = 1121) and Moldova (N = 939) in Reading, Math, Science, English as a foreign language, Music, and Art mastery motivation. Findings indicated that subject-specific mastery motivation (SSMM) domains in Hungary and Moldova have different paths across grade levels. In Hungary there was a constant decreasing trajectory across all grades in all domains with the exception of English whereas in Moldova the decrease is identified in Math, English, Music and Art between the fifth and the seventh grades but not between the seventh and the ninth grades, while reading mastery motivation levels remained stable. Upon conducting a cross-cultural comparison of SSMM levels across countries and grades, we identified only one statistically significant difference in science mastery motivation. The study attempts to explain the absence of cross-cultural differences not only through a conventional lens focusing on the unique characteristics of individual educational systems, but also by considering the cultural values associated with each country.This is a provisional file, not the final typeset articleThe investigation of subject-specific mastery motivation has been conducted using several samples from Hungary, Taiwan, and the Republic of Moldova, with the aim of elucidating the influence of culture on mastery motivation in academic context (